Cellular gene expression altered by human cytomegalovirus: Global monitoring with oligonucleotide arrays - Zhu, Hua (The National Academy of Sciences, 1998)
Mechanistic insights to viral replication and pathogenesis generally have come from the analysis of viral gene products, either by studying their biochemical activities and interactions individually or by creating mutant viruses and analyzing their phenotype. Now it is possible to identify and catalog the host cell genes whose mRNA levels change in response to a pathogen. We have used DNA array technology to monitor the level of ≈6,600 human mRNAs in uninfected as compared with human cytomegalovirus-infected cells. The level of 258 mRNAs changed by a factor of 4 or more before the onset of viral DNA replication. Several of these mRNAs encode gene products that might play key roles in virus-induced pathogenesis, identifying them as intriguing targets for further study.